Review of the third edition of adult and pediatric urology - Howards, Stuart S (Mosby, 1996)
Provides basic science and clinically relevant questions, answers, and rationales that aim to pinpoint areas needing further study in preparation for exams or recertification. The questions in this text were drawn from \"Adult and Pediatric Urology\".
Keywords: Urology; urologie; nefrologie